2008
DOI: 10.1016/j.ajhg.2008.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Two CES1 Gene Mutations Lead to Dysfunctional Carboxylesterase 1 Activity in Man: Clinical Significance and Molecular Basis

Abstract: The human carboxylesterase 1 (CES1) gene encodes for the enzyme carboxylesterase 1, a serine esterase governing both metabolic deactivation and activation of numerous therapeutic agents. During the course of a study of the pharmacokinetics of the methyl ester racemic psychostimulant methylphenidate, profoundly elevated methylphenidate plasma concentrations, unprecedented distortions in isomer disposition, and increases in hemodynamic measures were observed in a subject of European descent. These observations l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
256
3
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(277 citation statements)
references
References 24 publications
16
256
3
2
Order By: Relevance
“…Rare nonsynonymous variants in CES1 encode enzymes with impaired activities that dramatically alter the pharmacokinetics and drug response to the psychostimulant methylphenidate. 45 Several CES2 variants have been shown to be functionally deficient, and some have decreased esterase activities toward the anticancer agent irinotecan. 46 CES are clearly important in a variety of pharmacogenetic phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Rare nonsynonymous variants in CES1 encode enzymes with impaired activities that dramatically alter the pharmacokinetics and drug response to the psychostimulant methylphenidate. 45 Several CES2 variants have been shown to be functionally deficient, and some have decreased esterase activities toward the anticancer agent irinotecan. 46 CES are clearly important in a variety of pharmacogenetic phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…[2,8] Although their functional consequences remain uncertain, several CES1 variants have been reported in NCBI SNP database. The CES1 allele and estimated haplotype frequencies showed significant differences between African and European populations.…”
Section: Tcpmentioning
confidence: 99%
“…[2,6,7] In-vitro functional studies have demonstrated that the G143E and the D260fs variants have reduced catalytic function, resulting in the disruption of hydrolytic activity of CES1. [8,9] In a single-dose pharmacokinetic study, these two CES1 mutations were identified in one subject who displayed 7-fold higher total methylphenidate (i.e., combined d-and l-isomers) concentrations compared to that of other subjects (n=19). [2,9] In addition, -75T>G polymorphism was associated with the reduced appetite in attention deficit-hyperactivity disorder (ADHD) youths treated with methylphenidate [10] and the isoniazid-induced hepatotoxicity in latent tuberculosis infection patients.…”
Section: Introductionmentioning
confidence: 99%
“…The monitorization study which is conducted by positron emission tomography (PET) revealed that dopaminergic changes in brain may have huge personal variety [18]. Because of polymorphism of carboxylesterase 1 enzyme which metabolize MPH primarily, MPH rises to unexpected high doses [17,19]. Although it is not clearly denoted as psychosis, another group which is prone to stimulants' adverse effects is the group who has neurodevelopmental disorders like mental retardation and autism [13].…”
Section: Discussionmentioning
confidence: 99%